Issues of diagnostic search of soft tissue sarcoma - A. N. Sergeev; D. A. Maksimov; A. M. Morozov; M. A. Belyak; E. V. Penyaz'; M. O. Popova (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Soft tissue sarcoma is a heterogeneous group of relatively rare types of tumors, which demonstrates a huge variety of anatomical localization and histopathological characteristics. The rarity of soft tissue sarcomas combined with a variety of subtypes, forms of growth, progression and frequency of relapses makes it difficult to study them, make a correct diagnosis and early referral of patients for specialized care.The purpose of study. To analyze the problem of differential diagnosis of malignant and benign soft tissue neoplasms.Materials and methods. In the course of the work, current literary sources of domestic and foreign authors on a given topic were analyzed.Results. Since it is absolutely impossible to determine the clinical features of the presented sarcoma, soft tissue tumors showing any of the following signs are considered malignant until the opposite is proven: increasing in size, >5 cm, deeply located and/or painful. The greater the number of these clinical signs present, the higher the risk that the soft tissue tumor will turn out to be malignant; at the same time, an increase in size is the best individual indicator. It is worth noting that the absence of concomitant constitutional symptoms, such as fever, chills, night sweats or unintentional weight loss, should not reduce the doctor's suspicion of malignancy.Conclusion. In order to avoid erroneous diagnoses, a standardized diagnostic approach should be followed, starting from the moment of collecting the patient's medical history, clinical examination and ending with the use of appropriate imaging methods and biopsy.